Answer:
y = 3^(1 + x)
Step-by-step explanation:
Notice that each time x increases by 1, y increases by a factor of 3.
Thus, the required equation has the form y = 3^x.
Check: If x = 0, do we get 3? No. Therefore we must modify the exponent:
y = 3^(1 + x)
Check: If x = 0, do we get 3? 3^(1 + 0) = 3 (correct)
If x = 2, do we get 27? 3(1 + 2) = 3^3 + 27 (correct)
Answer:
k
Step-by-step explanation:
x=0 y=6
x=1 y=4
x=2 y=2
x=3 y=0
x=4 y=-2
x=5 y=-4
u basically get the pattern
1 is an odd number so let’s put 1 into n, (1)2+4 which equals 2+4 which is 6, 6 is not a prime number as it can has factors such as 2&3 not just 1&6.
Slope is rise/run
to find it we do (y1-y2)/(x1-x2)
y1 means the 1st y and y2 means the second y
in (x,y) form
y1=4
y2=4
x1=10
x2=7
(4-4)/(10-7)=0/3=0
slope is 0
Answer:
$462.50
Step-by-step explanation:
:))